Pengaruh Locus of Control, Role Stress, dan Fee Audit terhadap Kualitas Audit - Maria Agustina Munthe; Nurul Fachriyah (AKUNTANSI 45, 2026)
Audit quality plays an important role in maintaining the reliability of financial information and public trust in the public accounting profession. This study aims to examine the effect of locus of control, role stress, and audit fees on audit quality. The research uses a quantitative approach involving 103 auditors at Public Accounting Firms in East Java as the research sample. The sampling technique was carried out using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS 25. The results show that internal locus of control has a positive effect on audit quality, while external locus of control, role stress, and audit fees do not significantly affect audit quality. These findings indicate that audit quality is more influenced by internal factors, especially an individual's ability to control attitudes and responsibilities in audit implementation. In addition, this study provides important implications for Public Accounting Firm management in improving audit quality by strengthening auditors’ psychological aspects. It shows that character development, self-control, and auditor professionalism are key factors in maintaining consistent and trustworthy audit quality for the public. Furthermore, the results of this study are expected to serve as a reference for future research in auditing and behavioral accounting as well as the development of modern audit theory in Indonesia today.